METABOLISM CHARACTERISTICS OF SEAGRASS HALOPHILA SPINULOSA: CARBON DIOXIDE ABSORPTION RATE IN PHOTOSYNTHESIS AND OXYGEN USE IN RESPIRATION - Mashoreng, Supriadi; Rahman, Much. Faizal; Sadlie, Airine Universe; Tahir, Jasminati Nur (Jurnal Ilmu Kelautan SPERMONDE, 2022)
One of the roles of seagrass is as a carbon sink so its presence in the waters is very important. Each species of seagrass has a different character related to photosynthesis and respiration. The study was conducted to analyze the rate of carbon dioxide uptake in photosynthesis and the rate of oxygen use in respiration of Halophila spinulosa seagrass. The research was conducted in July 2022 in Puntondo Waters, Takalar Regency, South Sulawesi. Seagrasses were taken whole from waters 1 meter deep and then cleaned. The method used to analyze carbondioxide uptake and oxygen use was oxygen changes using clear and dark bottles. Each one shoot of H. spinulos was incubated using a clear and dark glass bottle with a volume of 270 ml. Incubation was carried out at 09.20 WITA (Middle Indonesian Time) - 12.20 WITA at a depth of 50, 100 and 150 cm with 5 replicate bottles at each depth. In addition, incubation of seawater (containing phytoplankton) was also carried out with 5 replicate bottles as a correction. At the beginning of incubation, the dissolved oxygen concentration in the water was measured. After incubation, oxygen was measured in clear and dark bottles. Seagrass leaves that have been used were scanned and analyzed using Image-J software to determine the extent. Seagrass leaves were dried in the oven, then weighed to determine the biomass. The results showed that carbon dioxide uptake per shoot ranged from 0.53 to 0.84 mgCO2/shoot/hour, per biomass 12.98-28.34 mgCO2/g/hour, and per leaf area 0.02-0.05 mgCO2/cm2/hour. The highest rate of carbon dioxide uptake was at a depth of 150 cm, both carbon uptake per shoot, biomass and leaf area. In contrast to the absorption of carbon dioxide, the rate of use of oxygen for respiration is highest at a depth of 50 cm. The use of oxygen per shoot ranged from 0.078-0.157 mgO2/shoot/hour, per leaf biomass 2.227-3.091 mgO2/g/hour and per leaf area 0.006-0.010 mgO2/cm2/hour.